1998
DOI: 10.1002/(sici)1521-379x(199807)50:7<292::aid-star292>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

A Biogradable Starch Based Coating to Waterproof Hydrophilic Materials

Abstract: In this work, the efficiency of starch acetylation to reduce water sensitivity of hydrophilic materials was investigated. Starch acetate was either included in foamed starch trays and/or used to coat these trays, wheat gluten based films or paper sheets. The water sensitivity of these foamed trays (quantity and kinetics of water uptake) is shown to decrease when starch acetate content of the foam increases. The coating of the hydrophilic trays with starch triacetate is detailled. The biodegradability of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 9 publications
0
19
1
4
Order By: Relevance
“…In this sense, to control the hydrophilic character of films, hydrophobic agents such as waxes and oils have been used, but these additives influence the mechanical properties. [13][14][15] Other researchers [16][17][18][19][20] have reported that starch acetylation can be used to decrease the hydrophilic character. A dual modification is a combined chemical treatment with the objective of taking advantage of each property obtained with the two modifications.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, to control the hydrophilic character of films, hydrophobic agents such as waxes and oils have been used, but these additives influence the mechanical properties. [13][14][15] Other researchers [16][17][18][19][20] have reported that starch acetylation can be used to decrease the hydrophilic character. A dual modification is a combined chemical treatment with the objective of taking advantage of each property obtained with the two modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Most applications, however, demand water insolubility. For this purpose, Fringant et al (1996) proposed the coating of foams with a more hydrophilic material such as acetylated starch 18. A second approach consists of foaming the acetylated starch directly instead of the pure starch 19.…”
Section: Introductionmentioning
confidence: 99%
“…Starch acetates are novel biodegradable polymers which undergo slower degradation and swelling than native starch. Fringant et al (1998) and Tuovinen et al (2004) used acetylated starch with a degree of substitution (DS) of 3 to improve the resistance of biodegradable materials to moisture. Ganjyal et al (2004) prepared starch acetate-corn fibre foams by extrusion.…”
Section: Starch Acetylationmentioning
confidence: 99%
“…Acetylation of starch decreases significantly the water absorption by PCL/starch blends. This observation is in agreement with the experiments of Fringant et al (1998) and Tuovinen et al (2004) .…”
Section: Mechanical Behaviourmentioning
confidence: 99%